Social Capital. Viewing Nordic Paths of Management - Noralv Veggeland (European Scientific Journal, ESJ, 2017)
How do Nordic states conduct policies in order to bring people closer to the socio-economic realm, in the sense that they, being social capital, tend to be integrated as active and participatory citizens? How do the interventionist and expensive Nordic welfare states survive in the global age, with demanding and ever changing claims to international competitiveness? This paper addresses these questions. Social capital and partnership building are introduced as terms and policy concepts in order to find answers in the framework of intended or unintended strategic endeavours. As a critical approach claims a contextual conceptualisation, we shall here view different European social models and administrative traditions in relation to comparative basic contexts in order to arrive at analytical answers. Leaning especially on the Anglo-Saxon model, the traditional Scandinavian universal welfare state model of the post-war Keynesian order has gradually been transformed into the contemporary Nordic model (Veggeland 2007). Contextual regulatory innovations and path-dependent processes have generated the survival of universal welfare state arrangements and collective action but with the mixed use of Market-Type Mechanisms (MTM) in the public sector of Anglo-Saxon origin. In summary, this blending of policies has resulted in the advantageous social capital of what is called flexicurity, social security combined with a flexible participatory labour market. We shall discuss both flexicurity policy and participatory subsidiarity defined downwards as contribution to an explanation of why the expensive welfare states of the Nordic type have not only so far been doing well but have also sustained both democratic and output-side legitimacy.